PENGGUN AAN DELAPAN LANGKAH DAN TUJUH ALAT (DELTA) UNTUK MEMPERBAIKI NILAI MATEMATIKA EKONOMI 1 DI FAKULTAS EKONOMI UNIVERSITAS SURABAYA - Widjaja, Stefanus Budy (Journal of Management and Business, 2003)
Nowadays implementation of quality management needs some techniques to collect information for managerial decision-making so continuous improvement process can be achieved. One of the important aspects in quality management is making decision base on facts or data. Facts or data could be collected through quality performance measurement and must be processed through statistical-analytical process. The Eight Steps and Seven Tools (DELTA in Indonesian Phrases, means DELapan langkah dan Tujuh Alat) is a statistical method that is developed to facilitate the quality improvement process, identify operational problems, and make the right actions to solve tire problems. The spreading of this successful method in Japan has been done by conducting periodic national convention on Quality Control Circle.This paper describes how to implement this method for solving the problem of teaching-leaming-process-improvement for Mathematical 1 subject in Faculty of Economics, the University of Surabaya. At the end, this paper discusses evidences that indicate about the usefulness of this method.